Roles of SAMHD1 in antiviral defense, autoimmunity and cancer. (25th April 2017) - Li, Miaomiao; Zhang, Dong; Zhu, Mengying; Shen, Yuxian; Wei, Wei; Ying, Songcheng; Korner, Heinrich; Li, Jun
Summary: The enzyme, sterile α motif and histidine‐aspartic acid domain–containing protein 1 (SAMHD1) diminishes infection of human immunodeficiency virus type 1 (HIV‐1) by hydrolyzing intracellular deoxynucleotide triphosphates (dNTPs) in myeloid cells and resting CD4+ T cells. This dNTP degradation reduces the dNTP concentration to a level insufficient for viral cDNA synthesis, thereby inhibiting retroviral replication. This antiviral enzymatic activity can be inhibited by viral protein X (Vpx). The HIV‐2/SIV Vpx causes degradation of SAMHD1, thus interfering with the SAMHD1‐mediated restriction of retroviral replication. Recently, SAMHD1 has been suggested to restrict HIV‐1 infection by directly digesting genomic HIV‐1 RNA through a still controversial RNase activity. Here, we summarize the current knowledge about structure, antiviral mechanisms, intracellular localization, interferon‐regulated expression of SAMHD1. We also describe SAMHD1‐deficient animal models and an antiviral drug on the basis of disrupting proteasomal degradation of SAMHD1. In addition, the possible roles of SAMHD1 in regulating innate immune sensing, Aicardi‐Goutières syndrome and cancer are discussed in this review.